Compensation for the Cost of a Surrogacy Arrangement in Personal Injury Cases - Sirko Harder (Bond Law Review)
A woman who has been rendered infertile by a defendant’s wrong may wish to obtain damages for the cost of becoming a parent through a surrogacy arrangement. Such a claim, which has yet to be brought before an Australian court, would raise two partially overlapping issues under Australian law. First, the claim must satisfy the general requirement that a person who has suffered personal injury can only recover expenses that are necessary and reasonable. Secondly, the laws of the Australian jurisdictions except the Northern Territory regulate surrogacy arrangements and criminalise commercial surrogacy arrangements (where the surrogate mother is promised a fee in addition to the reimbursement of expenses). This regulation may impact upon the recoverability of the cost of a surrogacy arrangement through the concepts of coherence of the law and public policy. The most complex scenario, but also the most likely to arise in Australian personal injury litigation, is that of a plaintiff who lives in Australia and wishes to enter into a commercial surrogacy arrangement in a foreign country in which this is lawful. This article investigates the legal issues that may arise if a claim for the cost of a surrogacy arrangement is brought before an Australian court.